Various approaches to the study of set expressions and the problem of their classification? - Baigarayeva, A. (KAZGUU Liberal Arts Digest Volume 2. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2022)
The paper aims at identifying various categorizations of phraseological units used in the English language. Therefore, the main purpose is to appeal to existing knowledge about the classification of sets of expressions and accordingly report the information. Moreover, discovered sorting techniques are applied to the evaluation of three well-known novels. The methodology of the research adopts six different sources that address the fluctuating tendencies in the way the authors separate PU (phraseological units) and summarize them; however, no other primary research is made. The results revealed that different analyses adversely fit cases and can be used for different purposes. Namely, Smirnitsky’s classification is practical for those who in studies languages, Logan Smith’s classification is useful for people dealing with the history and finally Vinogradov’s classification is essential for translators.
Keywords: Phraseology, phraseological units, set of expressions, idioms, idiom, classification, meaning, approaches, phraseological combinations, phraseological unities, phraseological fusions, compatibility